Makna Inklusivitas Perjamuan Kudus sebagai Ruang Perjumpaan dengan Penyandang Disabilitas - Tohata, Debbie (Asosiasi Teolog Indonesia, 2023)
This article considers Holy Communion as a meeting space of meaningful inclusivity for people with disabilities. While God’s initiative extends to all Christians to share together in table fellowship, individuals with disabilities are often less involved in the act of Holy Communion. Given conditions such as blindness, paralysis, and cognitive impairment, these Christians are frequently viewed as objects of compassion. Moreover, disabilities are often perceived in certain cultures as a result of parental or communal sins. Instead of regarding the disabilities of such persons as a symptom of sin, we must recognize that people with disabilities possess gifts bestowed by God for their life’s journey (Nancy L. Eiesland). The church, which is often indifferent to the challenges faced by people with disabilities, suffers from a lack of understanding of Christ’s role in the lives of people with disabilities (Michael S. Beates). As such, cultural values of shame felt by families often cause them to feel embarrassed about bringing their children to church or undergoing the catechetical process for their participating in Holy Communion. In contrast, the profound inclusivity of Holy Communion can help people understand that all are equal before Christ, and everyone deserves to participate in Holy Communion, accept salvation, and participate in fellowship with Christ. The church needs further education to understand Holy Communion as welcoming of everyone to encounter Christ in salvific faith and the truth that they are accepted as they are.